Mitigation of Salinity Stress in Wheat Seedlings Due to the Application of Phytohormone-Rich Culture Filtrate Extract of Methylotrophic Actinobacterium Nocardioides sp. NIMMe6 - Meena, Kamlesh K.; Bitla, Utkarsh M.; Sorty, Ajay M.; Singh, Dhananjaya P.; Gupta, Vijai K.; Wakchaure, G. C.; Kumar, Satish (Frontiers in Microbiology, 2020)
Salinity stress is an important plant growth limiting factor influencing crop productivity negatively. Microbial interventions for salinity stress mitigation have invited significant attention due to the promising impacts of interactive associations on the intrinsic mechanisms of plants. We report the impact of microbial inoculation of a halotolerant methylotrophic actinobacterium (Nocardioides sp. NIMMe6; LC140963) and seed coating of its phytohormone-rich bacterial culture filtrate extract (BCFE) on wheat seedlings grown under saline conditions. Different plant-growth-promoting (PGP) attributes of the bacterium in terms of its growth in N-limiting media and siderophore and phytohormone [indole-3-acetic acid (IAA) and salicylic acid] production influenced plant growth positively. Microbial inoculation and priming with BCFE resulted in improved germination (92% in primed seeds at 10 dS m–1), growth, and biochemical accumulation (total protein 42.01 and 28.75 mg g–1 in shoot and root tissues at 10 dS m–1 in BCFE-primed seeds) and enhanced the activity level of antioxidant enzymes (superoxide dismutase, catalase, peroxidase, and ascorbate peroxidase) to confer stress mitigation. Biopriming with BCFE proved impactful. The BCFE application has further influenced the overexpression of defense-related genes in the seedlings grown under salinity stress condition. Liquid chromatography–mass spectrometry-based characterization of the biomolecules in the BCFE revealed quantification of salicylate and indole-3-acetate (Rt 4.978 min, m/z 138.1 and 6.177 min, 129.1), respectively. The high tolerance limit of the bacterium to 10% NaCl in the culture media suggested its possible survival and growth under high soil salinity condition as microbial inoculant. The production of a high quantity of IAA (45.6 μg ml–1 of culture filtrate) by the bacterium reflected its capability to not only support plant growth under salinity condition but also mitigate stress due to the impact of phytohormone as defense mitigators. The study suggested that although microbial inoculation offers stress mitigation in plants, the phytohormone-rich BCFE from Nocardioides sp. NIMMe6 has potential implications for defense against salinity stress in wheat.